Effects of Thermo-Mechanically Processed Soybean Meal on Nursery Pig Growth and Fecal Characteristics - Jessica L. Smallfield; Jason C. Woodworth; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt; Alan J. Warner; Chad W. Hastad; Sabrina T. May; Wesley P. Schweer; Chad M. Pilcher (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 1,254 mixed-sex pigs (PIC 800 × [Fast York A × PIC L02]; initially 12.4 ± 0.22 lb) were used in a 28-d study to evaluate the effects of thermo-mechanically processed soybean meal (TM-SBM; Provisoy; Cargill; Wayzata, Minnesota) on nursery pig growth and fecal characteristics. Pens of pigs were randomly allotted to one of five dietary treatments in a randomized complete block design with body weight (BW) and nursery entry date as blocking factors. There were 18 to 20 pigs per pen and 12 pens per treatment. The experimental diets were cornsoybean meal-based with increasing TM-SBM replacing soybean meal on a standardized ileal digestible (SID) Lys basis in the diet (0, 25, 50, 75, and 100% in phase 1 and 0, 12.5, 25, 37.5, and 50% in phase 2). Treatment diets were fed in two phases from d 0 to 7 (phase 1) and d 7 to 21 (phase 2) followed by a common diet from d 21 to 28 (phase 3). At the end of phases 1 and 2 (d 7 and 21), fecal samples were collected from three randomly selected pigs in each pen to determine fecal dry matter (DM). Fecal scoring was also conducted on collected fecal material using a 0 to 4 scoring system, with 0 indicating firm feces and 4 indicating diarrhea. From d 0 to 21 (experimental period), ADG and ADFI increased then decreased (quadratic, P ≤ 0.038) with the best performance observed when TM-SBM replaced 25 to 50% of the SBM in phase 1 and 12.5 to 25% in phase 2. Moreover, feed efficiency improved (quadratic, P = 0.036) with TM-SBM replacing 50 and 25% of the SBM in phases 1 and 2, respectively, but worsened thereafter. No differences were observed for ADG, ADFI, and feed efficiency during the common period (d 21 to 28). Overall (d 0 to 28), ADG and ADFI tended to increase then decrease (quadratic, P ≤ 0.089) with the best performance observed when TM-SBM replaced 25% of the SBM in phase 1 and 12.5% in phase 2. For fecal DM, a treatment × day interaction was observed (quadratic, P = 0.024) indicating that the response to added TM-SBM differed across days. On d 7, the greatest increase in fecal DM occurred when TM-SBM replaced 25% of the SBM SID Lys (quadratic, P = 0.004) but decreased with 50% replacement of SBM SID Lys and then remained relatively stable. There were no fecal DM treatment differences observed on d 21. In summary, increasing TM-SBM to replace up to 25 to 50% of the SID Lys of SBM in phase 1 and 12.5 to 25% in phase 2 resulted in improved growth performance throughout the experimental period. Fecal DM on d 7 was greatest when 25% of the SID Lys of SBM was replaced with TM-SBM in phase 1. Higher inclusions of TM-SBM above 50% of the SID Lys of SBM in phase 1 and 25% in phase 2 were associated with decreased ADG and worsened feed efficiency.
Keywords: fecal dry matter; nursery pig; specialty soy protein